Upaya Pengembangan Perpustakaan Digital Dalam Melayani Pemustaka Difabel Secara Inklusif - Al Fadjri, Muhammad; Fenny Purwani, Fenny Purwani (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2022)
The development of information and communication technology in the form of digital, libraries have changed their form from conventional to digital which is often referred to as 'digital libraries' or digital libraries. The existence of the digital library itself is the same as its name which is in digital form so that it can be accessed anywhere and anytime through Android phones, tablets, notebooks, laptops and computers connected to the internet network. Digital libraries are not only useful for non-disabled users but all types of users including disabled users. The writing of this article is carried out using qualitative research methods with data collection techniques carried out by means of literature studies to obtain theoretical references related to the problem being studied through library materials from various reference sources. A digital library or digital library is an organized system consisting of hardware, software, electronic collections, and librarians or library staff who are responsible for collecting and managing them. Efforts in developing digital libraries include: Smooth and fast internet access, Preparation of hardware and software, Publication and socialization, Cooperation system, and Creativity. Furthermore, disabled users are users who have physical deficiencies so that they have special needs in accessing information. The existence of inclusive services means that librarians should not distinguish between non-disabled users and disabled users.